Integrating Artificial Intelligence into Arabic Textbook Evaluation: A Linguistic Analysis Based on Al-Fawzan’s Framework - Nadhif, Muhammad Ilham; Rizal Firdaus; Fahmi Ridha (Alibbaa’: Jurnal Pendidikan Bahasa Arab, 2026)
This study evaluates the linguistic dimension of Durus al-Lughah al-’Arabiyyah li Ghayr al-Natiqin Biha (Book I) based on Abdul Rahman Al-Fawzanâ€™s framework and explores the role of artificial intelligence (AI) in supporting textbook evaluation. Using a qualitative content analysis approach, the study examined selected linguistic materials, including vocabulary, grammatical structures, dialogues, and reading texts. A humanâ€“AI collaborative procedure was employed, in which AI assisted in identifying linguistic patterns and organizing data, while pedagogical interpretation remained under the researcherâ€™s responsibility. The findings indicate that the textbook strongly fulfills the criteria of using Standard Arabic without intermediary language and employing dialogue as the primary instructional entry point. However, the integration of language elements with language skills and the comprehensive treatment of language skills were only partially fulfilled. The study also demonstrates that AI can support textbook evaluation by facilitating the identification of recurring linguistic patterns and structural relationships. Nevertheless, pedagogical judgment and contextual interpretation still require human expertise. The findings suggest that AI is most effective as an analytical assistant rather than an autonomous evaluator in Arabic textbook evaluation.